Women, work and welfare in the Middle East and North Africa : the role of socio-demographics, entrepreneurship and public policies - Chamlou, Nadereh, 1956-; Karshenas, Massoud (London ; New Jersey : Imperial College Press, 2016)
'In the aftermath of the Arab Spring, and in light of socio-economic and geopolitical challenges facing governments old and new, women's rights and empowerment have gained new urgency and relevance. Groups in power, or groups contesting for power, are more conservative than expected, and there are serious threats to roll back some of the gains women had achieved over the past 20-30 years on economic and social fronts. The global gender debate has neglected the economic dimension of women's empowerment and a great deal of debate and interest among researchers is needed to push the topics further. This timely book brings together leading regional researchers to offer original research linking gender equality with economic policy, reinforcing the agenda from a broad-based perspective.'--Publisher summary.
Includes bibliographical references and index.
Keywords: Women -- Middle East -- Economic conditions -- 21st century; Women -- Africa, North -- Economic conditions -- 21st century; Women -- Employment -- Middle East -- 21st century; Women -- Employment -- Africa, North -- 21st century; Businesswomen -- Middle East; Businesswomen -- Africa, North; Women -- Government policy -- Middle East; Women -- Government policy -- Africa, North